Evaluasi Kinerja dalam Organisasi Kependidikan - Moh. Nasir (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2022)
Performance evaluation is a method and procedure for evaluating and monitoring the performance of a person, group, or institution in accordance with performance standards or goals that have been determined in an educational institution or organization. The fairest way to reward employees is through performance reviews. Performance evaluations are conducted to ensure that educational institutions are meeting their goals and objectives, as well as to find out where they stand and how well they are achieving their goals. It is very important to find out if there are delays or deflections so that they can be corrected immediately so that the goals or targets are met.